2012
DOI: 10.1007/s00345-012-0928-8
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of outcome and toxicity after salvage prostatectomy, salvage cryosurgery and salvage brachytherapy for prostate cancer recurrences after radiation therapy: a multi-center experience and literature review

Abstract: This overview shows clinical practice of prostate cancer salvage. Significant failure and toxicity rates are observed, regardless of salvage technique. Patients should be selected with great care before offering these salvage treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 28 publications
0
34
0
Order By: Relevance
“…1 Although a wide variety of potential salvage treatment methods exist, all come with potentially increased local toxicity risk versus primary treatment, which limits their use. 2,3 Salvage radical prostatectomy has been used with efficacy in carefully selected cases, but at the cost of a higher local complication rate versus de novo radical prostatectomy. [4][5][6][7] Selective implantation of an artificial urinary sphincter reduced the incidence of incontinence in 1 salvage prostatectomy series.…”
Section: Introductionmentioning
confidence: 99%
“…1 Although a wide variety of potential salvage treatment methods exist, all come with potentially increased local toxicity risk versus primary treatment, which limits their use. 2,3 Salvage radical prostatectomy has been used with efficacy in carefully selected cases, but at the cost of a higher local complication rate versus de novo radical prostatectomy. [4][5][6][7] Selective implantation of an artificial urinary sphincter reduced the incidence of incontinence in 1 salvage prostatectomy series.…”
Section: Introductionmentioning
confidence: 99%
“…In total, 10 papers from seven studies with 1252 patients (561 for CS vs RT, 745 for CS vs RP and 54 for both) were finally included for pooling in our study567891011121314 (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Seven papers567891011 from five studies reported the comparison between CS and RT, from which two articles78 based on one study presented results in mean follow-ups of 37 months and 105.2 months, respectively, results from one study were presented simultaneously in two papers910. Both these studies were RCTs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations